2012
DOI: 10.9710/kjm.2012.28.2.081
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Clithon retropictus (von Martens in Kobelt, 1879, Gastropoda: Neritidae) in Jeju Island, Republic of Korea

Abstract: The neritid species Clithon retropictus inhabits rivers and estuaries along the southern coast of the Korean mainland but has not been previously reported from Jeju Island. In 2007 and 2011 specimens of this species were obtained from two separate localities on the south coast of the island. Comparisons were made with von Martens' original description, specimens from the Korean mainland, and illustrations and descriptions in the literature. Although there were some differences in color and markings, and slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Of the identified SSRs, 68.42% were di-nucleotide repeats; this was followed by 16.99% tri-nucleotide repeats and 14.59% tetra/penta/hexa-nucleotide repeats ( Table 4 ). The predominance of di-nucleotide repeats in the unigene sequences of C. retropictus is in agreement with findings of SSRs in invertebrates, including molluscs [ 12 , 50 , 57 ]. Mononucleotide repeats were not included in the SSR screening as they may be the result of homopolymer generation, which is common in Illumina sequencing.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Of the identified SSRs, 68.42% were di-nucleotide repeats; this was followed by 16.99% tri-nucleotide repeats and 14.59% tetra/penta/hexa-nucleotide repeats ( Table 4 ). The predominance of di-nucleotide repeats in the unigene sequences of C. retropictus is in agreement with findings of SSRs in invertebrates, including molluscs [ 12 , 50 , 57 ]. Mononucleotide repeats were not included in the SSR screening as they may be the result of homopolymer generation, which is common in Illumina sequencing.…”
Section: Resultssupporting
confidence: 89%
“…In South Korea, this neritid species has been reported to exist in Jeollanam-do (South Jeolla Province), Gyeongsangnam-do (South Gyeongsang Province), and Jeju-do Island [ 9 , 10 , 11 , 12 ]. The details of this species, including shell morphology and ecology, were first determined from studies on the south coast of Jeju Island, after which it was identified from under rocks adjacent to a dry river bed on a muddy substrate along the north coast [ 7 , 12 ]. C. retropictus was also identified from a shell drift at Yaerae-dong, on the southern coast of Jeju Island and from a small, shallow brackish-water estuary southwest of Gangjeong Town.…”
Section: Introductionmentioning
confidence: 99%
“…Based on molecular barcoding of egg masses we provide evidence that the rare species N. concinnus, which has hitherto been known from Japan (Dunker 1861;Kabat and Kilias 1991), South Korea (Noseworthy et al 2007), and the Indo-West Pacific (Poppe 2008), also occurs in the northern Great Barrier Reef. Our findings support earlier studies (Huelsken et al 2008) demonstrating the usefulness of molecular barcoding of egg masses and phylogenetic analyses in the identification of naticid species.…”
Section: Discussionmentioning
confidence: 93%
“…Through analysis of fatty acid profiles and the sulfur-stable isotope, Zhukova et al (1992) [26] and Kharlamenko et al (2001) [27] have affirmed that P. pisidium in seagrass beds in Vladivostok, Russia, harbor chemolithoautotrophic bacteria, potentially pivotal in neutralizing phytotoxins accumulated in the seagrass bed sediments. Furthermore, various studies have documented the presence of P. pisidium in intertidal areas along the south coast and Jeju Island in South Korea [28][29][30]. Nevertheless, the molecular identification and phylogenetic affiliation of P. pisidium in Korean waters remain unresolved.…”
Section: Introductionmentioning
confidence: 99%